EFEITO DO SABIÁ (Mimosa caesalpiniifolia) NO CONTROLE DE NEMATÓDEOS GASTRINTESTINAIS EM CAPRINOS SUPLEMENTADOS A PASTO - SILVA, Ellen Cristina Vale (2020)
The infections caused by gastrointestinal nematodes are one of the main reasons for productivity reduction in goat livestock Approaches of control were being in a study with the aim of interrupting the parasites cycle, with less environmental impact and without causing anthelmintic resistance. The use of nutraceutical compounds, such as vegetables with a high concentration of condensed tannins (CT) with anthelmintic proprieties has been presented as an alternative in the control. Mimosa caesalpiniifolia is a shrub rich in tannins consumed by small ruminants in Brazil. This survey evaluated the anthelmintic effect of M. caesalpiniifolia in vivo in the control of gastrointestinal nematodes in goats supplemented in the cattle pasture. The leaves were collected, dried and ground into a powder. Twenty goats, anglo-nubianos, aged between six and eight months and with a body weight mean of 15,0 ± 2,5 kg were utilized in the experiment. The animals were naturally infected in a pasture of Panicum maximum cv. Massai in the experimental sector of Ovinocaprinoculture of the Federal Institute of Maranhão - IFMA, Campus São Luís Maracanã. They were divided into two groups based on fecal egg count and the body weight. The control group received a concentrate without condensed tannins and the treated group received a concentrate and leave powder of M. caesalpiniifolia. All animals were supplemented with iso-protein and iso-energetic, and daily access to the pasture from 8 AM until 4 PM. The supplement was provided when the animal returned from the pasture, and the quantity supplied was determined according to animal body weight (3,07% of live weight), the animals were weighed weekly and the quantity of food was readjusted. The goats were kept in experimental sheds for 7 days during an adaptation period, with water and specific minerals were supplied ad libitum. The animal's stool collection, conjunctiva inspection, and hematocrit were realized in an interval of 3 days. The experiment was started D0 when the infection was confirmed and lasted for 25 days.The animals were euthanized following the FAMACHA degree and hematocrit with the respective values, 4: between 13 and 17% and 5: 12 % and below. Also, the presence of submandibular edema and/or diarrhea were verified. They were humanely euthanized and a load of nematodes was estimated. The addition of M. caesalpiniifolia leaves power did not influence the animal’s body weight in the different groups studied (P> 0,05). An effect was shown only on the D3 and D9 groups (p<0,05). On the contrary, no significant difference between groups in the other days (p>0,05). In the coproculture, the prevalent genera were: Haemonchus sp., Trichostrongylus sp., Oesophagostumum sp. and Cooperia sp. respectively. Also, it was found Moniezia sp. and oocysts of Eimeria sp. in an inconsistent and variable number. Furthermore, in the D25 70% of the animals from the control group were euthanized following the clinical signs. In comparison, the other treated group with CT was capable of resisting the infection effects. The nematodes species found were: Haemonchuscontortus, Trichostrongylusaxei, Oesophagostumum sp., Trichurismuris. There was no significative effect of the M. caesalpiniifolia supplementation in the reduction of the adult nematodes burden on the abomasums, small intestine and large intestine to both groups. (P>0,05). Even though the low anthelmintic activity in animals with a heavy infection, there is a greater survival of animals which received the M. caesalpiniifolia supplementation.